Suicide risk factors of royal thai police officers - Veerapol Gulabutr (Mahidol University. Mahidol University Library and Knowledge Center, 2023)
This was a quantitative and qualitative research aimed to study the level of suicide factors among the Royal Thai Police Officers, to investigate the social, surroundings, and the psychological aspects causing suicide among the Royal Thai Police Officers as well as to find the prevention and the solution to the suicide problem. The quantitative method was used to collected data from 977 police officers under the Provincial Police Region 3, 5 and the Headquarter of the Metropolitan Police Bureau using questionnaires while the in-depth interview with 8 qualified supervisors was conducted to obtain qualitative data from the officers who were involved in the crime prevention policy in the police including 9 Physician and a Psychologist. Statistics used for data analysis were percentage, mean, standard deviation, the t-test (Independent Samples Test) the F-test (One-Way ANOVA) and Structural Equation Modeling: SEM by AMOS program. The study indicated that majority of the police officers were male Police Senior Sergeant Major, working in the suppression line of the Metropolitan Police Bureau, aged between 41-50 years, operated for 21-30 years in the government civil service, Buddhist, married with no children, and graduated with a bachelor's degree. Factors that affected the suicide risk level of the Royal Thai Police officers were social factors, the surroundings and psychological factors. These, consisted of disputes in the family, having congenital disease, inadequacy of income, pressure from work, Suicide history in family or had been prosecuted. These factors were significantly associated with the Thai police officer's suicide statistically significant at 0.05 levels. In addition, the result indicated that depression and impulsiveness were significantly related to suicide among the Thai police officers statistically significant at 0.05 levels as well. This study suggested that 1) In terms of policy; the Royal Thai Police should focus on how to optimize personal selection and development to increase personal efficiency. 2) In practice, psychological test by the experts should be implemented to help identify the risk group, and find a solution to prevent suicide risk. Furthermore, mental development training should be continuously and consistently conducted among the police officers at all levels so that all of them would have strong mental state, be mindful in problem solving towards trouble issues, realize the right solution, be optimistic and be worthy in society, family and friends